Effects of severe plastic deformation on grain refinement and martensitic transformation in a metastable β Ti alloy. Issue 1 (July 2015) - Zafari, A; Wei, X S; Xu, W; Xia, K
Abstract: A Ti-5553 metastable β alloy was subjected to high pressure torsion (HPT) to obtain a nano β grain structure. The β grains were dramatically refined from an initial size of ∼1 mm to < 50 nm during HPT. The stress induced martensitic α" plates divided β grains into smaller domains and enabled subgrains to form even in very fine grains. The reverse α" to β transformation occurred when the thickness of the α" laths reached < ∼10 nm, leading to pure β nano-grains. Further deformation to an equivalent strain of 242 resulted in grain growth and the formation of well defined grain boundaries.